ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA BIDAN DALAM PELAYANAN ANTENATAL CARE DI PUSKESMAS KAGOK KOTA SEMARANG - Rahma Kusuma Putri Widyani; Anneke Suparwati; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Antenatal care is health care that given to mother in their pregnancy according the set standard. In 2013 and 2014, K1 and K4 indicators in Kagok Health Primary Care hasn’t reach the minimal healthcare standard yet. The aim of this research is to analyze the performance of the midwife in Kagok Primary Health Care, Semarang, looked by the variables of : leadership of head of the Primary Health Care, resources, motivation, supervision, and structure and job design. This research was observational research with analytical approach. The data collected by in-deepth interview to the main informant, is the midwife and to do validity test, triangulation was done on the head of primary health care and Health Departement of Semarang City’s workers. The result of this research is the leadership of the primary health care are still lack, resources are limited, motivation and supervisition are still lack, structure and job design are still not according to the standard. Recommended to Kagok Primary Health Care Semarang to give motivation like coaching, guidance, additional incentives and held an forum about complaint felt by the midwife during work. To Health Departement of Semarang is expected to do the monitoring, guidance, oversight and supervision to the head of the health centers and midwife regularly and scheduled